Effects of Anthropometric Variables and Seat Height on Automobile Drivers' Preferred Posture With the Presence of the Clutch. (March 2018) - Peng, Junfeng; Wang, Xuguang; Denninger, Lisa
Objective: The effects of seat height and anthropometric dimensions on drivers' preferred postures were investigated using a multiadjustable vehicle mock-up with a large number of adjustments and extended ranges. Background: Many studies have been conducted on preferred driving posture under different test conditions showing mixed and even contradictory findings. No studies thus far have considered the clutch and compared Chinese and European drivers. Method: Four seat height conditions were tested: free and three imposed heights (250, 300, and 350 mm). Sixty-one subjects (40 French-born and 21 Chinese-born) participated in the experiment, covering a large range of stature and sitting height–to–stature ratio. The RAMSIS kinematic model was used to reconstruct postures, and main intersegmental angles were extracted for characterizing posture. Results: Under the free seat height condition, no significant differences in preferred intersegmental angles were observed between different participant groups. Seat height mainly affected trunk–thigh angle, whereas it had almost no effect on trunk orientation and other intersegmental angles. Chinese participants sat more forward in the seat, leading to a more opened trunk–thigh angle and a more reclined trunk. Conclusions: Results suggest that intersegmental angles of preferred posture are not dependent on anthropometric dimensions, although shorter drivers prefer a slightly less reclined trunk. Self-selected driving posture results from a compromise between maintaining the intersegmental angles in one's preferred range and a preferred trunk orientation in space. Applications: The findings contribute to a better understanding of preferred driving postures and would be helpful for improving vehicle interior design.